Identification of exotic temperate maize inbreds for use in tropical breeding programs - Ndoro, Ozwell; Magorokosho, Cosmos; Setimela, Peter S.; Casper Nyaradzai Kamutando; Labuschagne, Maryke (Springer, 2022)
Restricted genetic variability in elite tropical maize germplasm has raised concerns about the potential to develop higher yielding and stress-tolerant varieties. Elite temperate germplasm has high levels of genetic diversity for yield, drought tolerance and earliness. The objective of this study was to identify temperate maize inbreds that could enhance the grain yield potential, drought tolerance and high plant density tolerance of adapted tropical germplasm. Two hundred and forty-three temperate inbreds with expired Plant Variety Protection Act certificates from the USA were crossed to three CIMMYT single-cross testers. The three-way testcrosses were evaluated under high density, optimal, low nitrogen and managed drought conditions. Among the outstanding exotic temperate inbreds were HB8229, W8304, LH198 and PJH40 from the stiff stalk group, and LH159, LH214, and LH23Ht from the non-stiff stalk group. Of the highest yielding testcrosses, 65% were heterotic group A-lines, 30% heterotic group B-lines, and 5% were AB-lines. Although the testcrosses were more susceptible to diseases, their grain yield was comparable to the commercial checks, especially under managed drought and high-density conditions. Temperate lines also induced earliness and shorter plant stature to the three-way crosses.